So the task says:

for $\alpha_1\ldots,\alpha_n, \beta\in \mathbb R$, we define $U = \{(x_1\ldots,x_n) ∈ \mathbb{R}^n \,|\, \sum_{i=1}^n \alpha_ix_i = \beta\}$. When is the $U$ subspace?

I know that if subspace is a subspace only if $x,y∈ U$ and $A,C ∈ \mathbb R$ this is true:

$Ax + Cy ∈ U$,

I could not find the answer so i checked the answer.

enter image description here

I understand everything in explanation except the last part where it says that B needs to be 0 can someone explain to me why $\beta$ needs to be 0.

Thank you!

  • 2
    $\begingroup$ Well if $B$ is not zero then 0 is not in the subspace. $\endgroup$ – Calvin Khor Jan 20 at 19:34
  • $\begingroup$ Of course, but the OP wanted to understand that specific proof. $\endgroup$ – José Carlos Santos Jan 20 at 20:13
  • $\begingroup$ Ok thank you! But what if µ = 1/2 and λ = 1/2 than if B is diffrent than 0, (1/2 * B) + (1/2*B) = B $\endgroup$ – Petar Jan 20 at 20:35

Because if $\beta\neq0$, then you take, say, $\lambda=\mu=1$, and then it will be false that $\lambda\beta+\mu\beta=\beta$, since then this would mean that $2\beta=\beta$.

  • $\begingroup$ Ok thank you! But what if µ = 1/2 and λ = 1/2 than if B is diffrent than 0, (1/2 * B) + (1/2*B) = B $\endgroup$ – Petar Jan 20 at 20:05
  • $\begingroup$ If $\mu=\lambda=\frac12$, you deduce nothing. But the proof says that for all real $\mu$ and $\lambda$ we have $\mu\beta+\lambda\beta=\beta$. So, I used $\mu=\lambda=1$ to reach a contradiction. That's all. $\endgroup$ – José Carlos Santos Jan 20 at 21:34
  • $\begingroup$ Ok thank you! I understand it now. $\endgroup$ – Petar Jan 20 at 21:51
  • $\begingroup$ If my answer was useful, perhaps that you could mark it as the accepted one. $\endgroup$ – José Carlos Santos Jan 20 at 21:53
  • $\begingroup$ yes i did it now ,tnx $\endgroup$ – Petar Jan 20 at 22:09

Notice that $\sum_1^na_ix_i$ is merely the dot product of $\mathbf x=(x_1,x_2,...,x_n)\in U$ with the vector $\mathbf a=(a_1,a_2,...,a_n)$. Given that vector $\mathbf x\in U\leftrightarrow\mathbf x\cdot\mathbf a=B$. Now, $\mathbf x,\mathbf y\in U\implies\mathbf x+\mathbf y\in U\implies(\mathbf x+\mathbf y)\cdot \mathbf a=\mathbf{x\cdot a}+\mathbf{y\cdot a}=B+B=B$, that implies $B=0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.